Co-construcción de soluciones barriales participativas: Caso de estudio barrio Salapaca, de la parroquia Zumba, cantón Chinchipe, año 2022 - Jaramillo Vargas., Yesenia Yulisa (2023)
The purpose of the following research is to contribute to the proposal of participatory neighborhood solutions to the problems identified in the Salapaca neighborhood from the Chinchipe canton, province of Zamora Chinchipe, period 2022, as a result of the achievement of three specific objectives that: promoted the organization and participation of the inhabitants, participated in the formulation of collective diagnoses of neighborhood problems, and supported the development of solutions to the neighborhood's problems. A further point of interest is that the deductive and inductive methods were used because it was necessary to describe directly and indirectly the structural problems suffered by the neighborhood, so that they could be based on a specific framework. From tools focused on the four variables (infrastructure, signage, security and environment) that the project "Co-construction of Participative Neighborhood Solutions: Zone 7-Ecuador" manages, such as a first approach to the neighborhood, In order to support the development of this research, it was necessary to obtain information that generalizes the most relevant results of the problems found, using an observation sheet, surveys of household heads, and interviews with the neighborhood's president. Based on the main findings of this research, we were able to determine that: the nonexistence of sanitary sewerage service, poor roads, and poor public lighting were the three most pressing problems facing the neighborhood, which represented the most outstanding percentages as 100%, 80% and 60% respectively, because the residents show dissatisfaction with these situations and consider them as a priority; on the other hand it was determined that the theory of rational choice, used in this research allowed to identify how human beings have the ability to make decisions from an opinion either individually or collectively to solve the different problems identified as urgent.